The Chinese road to socialism : economics of the Cultural Revolution - Wheelwright, E.L.; McFarlane, Bruce; Robinson, Joan (Harmondsworth : Penguin Books, 1973)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: socialisme; Culturele Revolutie; China